Case report: Treatment-resistant schizophrenia with auto-aggressive compulsive behavior—Successful management with cariprazine - Renemane, Lubova; Rancans, Elmars (Frontiers in Psychiatry, 2023)
The present case report describes a patient with treatment-resistant schizophrenia and auto-aggressive compulsive behaviour who was effectively treated with a third-generation antipsychotic medication, cariprazine. The diagnosis was made 12 years ago, and the patient has been hospitalized 14 times and undergone various antipsychotic treatments. Despite receiving both inpatient and outpatient care, the patient's response to treatment has been only partial, and he has been classified as a treatment-resistant case. Therefore, the patient was switched to cariprazine, which led to significant improvements in both positive and negative symptoms, as well as the complete reduction of auto-aggressive compulsive behaviour. These improvements contributed to the patient's overall social functioning and the achievement of remission, while also avoiding polypharmacy and eliminating the metabolic side effects associated with previous treatments.